Design of Moral Education Management System for Higher Vocational Students Based on Multisource Sensing Data Fusion - Hui Guo (Discrete Dynamics in Nature and Society)
Based on the specific circumstances of colleges and universities, this study presents the moral education management system and leverages multisource sensor data and other technologies to develop an information system in line with the moral education management of modern college students. Using multisource sensor data fusion and learning data definition, the fused education data is expressed in a standardized way, resulting in a common and standard data interchange format. This foundation is used to build a shareable and reusable data management system that enables data sharing and interchange across multiple heterogeneous data sources, aids the intelligent education system in obtaining more comprehensive and complete recorded data, and improves data sharing timeliness. As a result, learning behavior analysis results are more objective, immediate, and accurate, allowing the intelligent education system’s response to be more prompt and intelligent. This study, which is based on multisource sensor data fusion, also discusses platform selection, system architecture, database design, and methods and suggestions for overcoming critical challenges and can be used as a reference for other university information management systems with vast amounts of data.